Rapidly Progressive Apical Hypertrophic Cardiomyopathy: Not Everything is What It Seems - Ahmed K. Mahmoud; Juan M. Farina; Kamal Awad; Milagros Pereyra; Isabel G. Scalia; Mohammed Tiseer Abbas; Timothy Barry; Said Alsidawi; Chadi Ayoub; Reza Arsanjani (Methodist DeBakey Cardiovascular Journal)
Apical hypertrophic cardiomyopathy (HCM) is a rare variant of HCM. A 43-year-old female with a past medical history significant for hypertension and kidney transplantation presented with recurrent syncopal episodes and dyspnea on exertion. Electrocardiogram showed characteristic diffuse giant T-waves inversion, and cardiac magnetic resonance showed HCM with circumferential apical thickening. This case highlights the rapid development of apical HCM and its challenging diagnostic characteristics.